The Impact of Agricultural Subsidies on the Corn Market with Farm Heterogeneity and Endogenous Entry and Exit - Stephen Devadoss; Mark J. Gibson; Jeff Luckstead (Journal of Agricultural and Resource Economics, 2016)
We develop a model with farm-level heterogeneity in productivity and endogenous entry and exit decisions to analyze the effect of price supports and direct payments on the U.S. corn market. The analytical results show that, contrary to the existing literature, removal of direct payments augments productivity while removal of price supports does not impact productivity, and direct payments can lead to larger production distortions than price supports under certain conditions. The simulation results corroborate the theoretical findings in that if both policies are equal in magnitude, then direct payments result in larger price, output, and welfare distortions than price supports.